Crown shape dynamics of dense mangrove Kandelia obovata stands in Manko Wetland, Okinawa Island, Japan - KANGKUSO ANALUDDIN; ANDI SEPTIANA; SAHADEV SHARMA; AKIO HAGIHARA (Biodiversitas Journal of Biological Diversity, 2016)
Analuddin K, Septiana A, Sharma S, Hagihara A. 2016. Crown shape dynamics of dense mangrove Kandelia obovata standsin Manko Wetland, Okinawa Island, Japan. Biodiversitas 17: 865-872. The objectives of this study were to elucidate the crown structure dynamics for dense mangrove stands, and to know the crown shape maintenances and its important role for ensuring the stability and vitality the crowded mangrove forest. The growth parameters of K. obovata Shue, Liu & Yong stands, such as tree height H (m), height at the lowest living leaves HL (m), crown length CL (m) and crown width CW (m), were measured in the summer from 2004 to 2008. The crown shape dynamics were analyzed. The results showed that the HL was significantly increased with increasing H, which suggests thatthe crown changed to be dumpy as the stands grew. However, the CL of young stands increased and then decreased continuously as the stands grew, while the CL of mature stands decreased from 2004 to 2007 and then increased in 2008. Meanwhile, the CL/CW ratio of young stands decreased as the stands grew, while the CL/CW ratio of mature stands decreased and then increased, which imply that dense Kandelia obovata trees might transform their crown shape for reducing of competition for light among trees. Therefore, these resultssuggested that the crown shape of dense mangrove treesare dynamics as developing stands.